Effect of Conventional and Ultrasonic Assisted Bleaching on Colour Fastness Properties of Reactive Dyed Cotton Fabric - Farooq, Assad; Azeem Ashraf, Muhammad; Mohsin, Muhammad (Asian Journal of Chemistry, 2013)
The uniformity of dyed cotton materials largely depends upon the efficiency of fabric preparatory processes. For uniform colouration all natural and added impurities from cotton are removed by scouring and bleaching by treating with harsh chemicals at elevated temperatures which consumes much of energy. The effective use of ultrasound in textile wet processing provide benefits such as reduced energy costs and increased product quality in less time. In this research work cotton fabrics were dyed after bleaching by conventional and ultrasonic assisted bleaching technique. Colour fastness properties of reactive dyed cotton fabrics such as washing, rubbing, ironing and light were determined and compared to evaluate the effect of bleaching. The study showed that pre-treatments have a significant effect on fastness properties of fabrics. The fabric samples dyed after ultrasonic bleaching clearly showed better fastness properties even at low temperature and time as compared to conventional technique.